PEMANFAATAN MEDIA DIGITAL DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM UNTUK MENINGKATKAN LITERASI KEAGAMAAN SISWA SEKOLAH DASAR: STUDI PADA SDN 108/IX DAN SDN 028/IX TANJUNG PAUH KECAMATAN MESTONG KABUPATEN MUARO JAMBI - Birma Yuliza; Fitriyani Kosasih; Eliva Sukma Cipta (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The rapid advancement of digital technology has significantly transformed educational practices, including the teaching of Islamic Religious Education (IRE) at the elementary school level. The integration of digital media into classroom instruction is expected to enhance students' religious literacy by providing more interactive, engaging, and meaningful learning experiences. This study aimed to analyze the utilization of digital media in Islamic Religious Education learning to improve the religious literacy of elementary school students at SDN 108/IX Tanjung Pauh and SDN 028/IX Tanjung Pauh, Mestong District, Muaro Jambi Regency. This research employed a qualitative approach using a case study design. Data were collected through classroom observations, in-depth interviews with school principals, Islamic Religious Education teachers, classroom teachers, and students, as well as documentation. The collected data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing. The findings revealed that the integration of digital media, including instructional videos, interactive presentations, educational applications, and internet-based learning resources, contributed positively to students' religious literacy. Students demonstrated greater engagement, improved understanding of Islamic concepts, enhanced critical thinking in evaluating religious information, and increased ability to apply Islamic values in their daily lives. The study also identified several challenges, including limited technological facilities, unstable internet connectivity, and varying levels of students' digital competence. Nevertheless, teachers successfully addressed these challenges through innovative instructional strategies and collaborative learning activities. Therefore, digital media can serve as an effective instructional tool for strengthening religious literacy and fostering meaningful Islamic Religious Education learning in elementary schools.